Fingertip traumatic amputations in children. Treatment with semiocclusive foil dressings-preliminary results - Dimitar Trizlov; Dimitar Raykov; Stoyan Ivanov; Ivan Trizlov (Journal of the Bulgarian Orthopaedics and Trauma Association)
Introduction: Traumatic fingertip amputations in childhood constitute 2% of all hand injuries in individuals under the age of 14. These injuries have a significant impact on the psychological and emotional well-being of both the children and their parents. The treatment is multifactorial, dependent on the severity and location of the injury, and can involve both conservative and surgical approaches.